Encapsulation of Hydrocortisone and Mesalazine in Zein Microparticles - Peter J. Halley; Roger A. Stanley; Stuart K. Johnson; Paul Dubois; Esther T. L. Lau; Steven J. Giddings; Salmaan G. Mohammed; Kathryn J. Steadman (MDPI AG, 2013)
Zein was investigated for use as an oral-drug delivery system by loading prednisolone into zein microparticles using coacervation. To investigate the adaptability of this method to other drugs, zein microparticles were loaded with hydrocortisone, which is structurally related to prednisolone; or mesalazine, which is structurally different having a smaller LogP and ionizable functional groups. Investigations into the in vitro digestibility, and the electrophoretic profile of zein, and zein microparticles were conducted to shed further insight on using this protein as a drug delivery system. Hydrocortisone loading into zein microparticles was comparable with that reported for prednisolone, but mesalazine loading was highly variable. Depending on the starting quantities of hydrocortisone and zein, the average amount of microparticles equivalent to 4 mg hydrocortisone, (a clinically used dose), ranged from 60-115 mg, which is realistic and practical for oral dosing. Comparatively, an average of 2.5 g of microparticles was required to deliver 250 mg of mesalazine (a clinically used dose), so alternate encapsulation methods that can produce higher and more precise mesalazine loading are required. In vitro protein digestibility revealed that zein microparticles were more resistant to digestion compared to the zein raw material, and that individual zein peptides are not preferentially coacervated into the microparticles. In combination, these results suggest that there is potential to formulate a delivery system based on zein microparticles made using specific subunits of zein that is more resistant to digestion as starting material, to deliver drugs to the lower gastrointestinal tract.